Terrorism, Religious and Ethnic Intolerance Issues in the Syllabuses and Textbooks of Bengali and English Medium and Madrasha Education in Bangladesh An Appraisal - Hoque, NM Sajjadul (Himalayan Journal of Sociology and Anthropology, 2014)
Bangladesh, a seventh largest populous and fourth largest Muslim country in the World, is often facing the problems of terrorism, religious and ethnic intolerance. There are many cases of terrorist activities, religious and ethnic intolerance in the recent past. Like many of the post-colonial societies, various national policies were adopted towards facing the challenges of terrorism, religious and ethnic intolerance in Bangladesh. One of the most important policies was formulating National Education Policy (NEP)-2010 though there are a large number of contradictions about the implementation of the NEP. Needless to say peoples of Bangladesh are the victims of terrorism, religious and ethnic intolerance. The Author’s perception is education itself a catalyst for social change and it is a powerful instrument in the process of overcoming the problems. In other words, author of this paper believe that syllabuses and text books of both general and madrasha education streams of Bangladesh have significant role in educating people to counter terrorism, religious and ethnic intolerance. However, an attempt has been made in this paper through reviewing the current syllabuses and text books of general and madrasha education streams and also through assessing the peoples’ opinions of Bangladesh to know whether the syllabuses and text books are adequately addressing the issues of terrorism, religious and ethnic intolerance or not. DOI: http://dx.doi.org/10.3126/hjsa.v6i0.10715 Himalayan Journal of Sociology and Anthropology Vol.6 2014: 146-165